PERAN TNI DI MASA PANDEMI COVID 19 DALAM PERSPEKTIF HUKUM DAN BELA NEGARA - Karlina, Arlis (Jurnal Hukum Statuta, 2022)
The TNI, as a national component, is involved in handling the COVID-19 virus and administering COVID-19 vaccinations throughout Indonesia. TNI soldiers have been actively involved on the front lines with Health Workers in battling the COVID-19 pandemic since it first entered Indonesia. The TNI's task in dealing with the epidemic is to carry out Military Operations Other Than War (OMSP), as mandated by TNI Law Number 34 of 2004, namely assisting the Regional Government's tasks and providing humanitarian assistance. As the enforcer of state sovereignty, the TNI plays a variety of roles, including economic, social, cultural, security, health, and logistics distribution. The urgency of TNI involvement in dealing with the COVID-19 pandemic is influenced by risk factors, specifically the very high rate of transmission of the COVID-19 disease outbreak, the ability of civil institutions to deal with COVID-19, and the impact of the COVID-19 pandemic on socioeconomic and political stability of Indonesia as a country.